TERCERABUT DARI AKAR; Isu LGBT di Bumi Melayu Riau - Harmaini, Harmaini; Irwandra, Irwandra; HM, Moh Said; Syafiah, Syafiah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research was grounded on the argument that Malay Society is know to be highly religious and Islamic, even identifying themselves as strong Muslims. However, the issue of LGBT has been increasingly prevalent in Riau since 2023. Employing a qualitative approach and utilizing literature studies, this research attempted to analyze issues related to LGBT in the Land of Lanang Kuning. Data were obtained through research findings on LGBT in Riau on Mendeley as well as from both print and online media. The findings indicated that the growing issue of LGBT in Riau is accompanied by an increase in positive sentiments and perceptions towards LGBT behavior. Several emerging studies demonstrated the reinforcement of positive sentiments and the high positive perception among Riau students towards LGBT.